2020
DOI: 10.1029/2019jb017781
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of Fault Rupture and Fluid Leakage in Shale: Insights From a Controlled Fault Activation Experiment

Abstract: We observed rupture growth caused by controlled fluid injections at 340‐m depth within a fault zone in the low‐permeability Opalinus Clay in the Mont Terri Underground Research Laboratory (Switzerland). The rupture mechanisms were evaluated using measurements of the three‐component borehole wall displacements and fluid pressure in two sections of the fault zone and located horizontally 3 m apart from each other. One section was set across a secondary segment of the fault and used for stepwise fluid injection i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 48 publications
1
50
0
Order By: Relevance
“…A detailed description of the hydromechanical response of the whole test sequence is given in Guglielmi et al (2020). Here, we focus on the pressure test conducted step-by-step with an engine pump ( Fig.…”
Section: E X P E R I M E N T R E S U Lt Smentioning
confidence: 99%
“…A detailed description of the hydromechanical response of the whole test sequence is given in Guglielmi et al (2020). Here, we focus on the pressure test conducted step-by-step with an engine pump ( Fig.…”
Section: E X P E R I M E N T R E S U Lt Smentioning
confidence: 99%
“…The borehole was initially dry (no flow was observed after drilling). After deployment of the probe and sealing of the injection interval by packer inflation, the injection chamber was saturated with a fluid with equivalent chemistry to the formation fluid and to an initial pressure of 0.6 MPa to be in equilibrium with the local formation pressure (Guglielmi 2016;Guglielmi et al 2020).…”
Section: Simfip Probementioning
confidence: 99%
“…Moreover, the slip orientation on the SE-dipping fractures is consistent with the first slip event, occurring during the pressurization of the interval located 3 m below the analyzed test. Guglielmi et al (2020) showed that this slip, occurring on a SE-dipping fracture (136°/32°), is favorable for activation under the stress state obtained by Martin and Lanyon (2003). Finally, the SW-dipping fractures are typically sealed with calcite and celestite (Nussbaum et al 2011), which adds cohesion and prevents the reactivation of these fractures.…”
Section: Isolating Displacement Events On Natural Reactivated Fracturesmentioning
confidence: 99%
See 1 more Smart Citation
“…In conventional coherent optical time-domain reflectometer (COTDR) method, Rayleigh backscatter spectrum generated for each region in the longitudinal direction of the optical fiber is obtained through measurement ( Fig. 1) (Hartog, 2017). From the frequency shift between the reference Rayleigh-scattering power spectrum (RSPS) and a target RSPS using the cross-correlation method, the strain or temperature change at the point can be calculated.…”
Section: Methodsmentioning
confidence: 99%